2011
DOI: 10.3384/ecp110571970
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Comfort Benefits of a Cool Roof Application in a Non-Residential Building Belonging to Roma Tre University

Abstract: Abstract:The Mediterranean architecture was characterized by passive solutions able to ensure thermal comfort conditions in the built environment during the hot season. This cultural heritage is almost disappeared, delegating the comfort conditions to artificial systems. One of the above mentioned passive solutions concerns the use of light colors to redirect most of the incident solar radiation. Cool roofs are a mix of these old concepts and modern technologies. The paper reports the results of a cool roof ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Besides, it is important to emphasise that the performance of the roof surface also depends on the thermal emissivity that drives the radiative exchanges of the roof with the sky and the surrounding objects. Several studies were carried out during the past years and showed the potentialities and limits of the technology by means of numerical analyses (Akbari, Bretz, Kurn, & Hartford, 1997;Christen & Vogt, 2004;Suehrcke, Peterson, & Selby, 2008;Synnefa, Santamouris, & Akbari, 2007;Zinzi, 2010) and monitoring in real buildings (Bozonnet, Doya, & Allard, 2011;Carnielo, Fanchiotti, & Zinzi, 2011;Kolokotroni, Gowreesunker, & Giridharan, 2011;Kolokotsa, Diakaki, Papantoniou, & Vlissidis, 2011;Paolini et al, 2013;Parker et al, 1998;Romeo & Zinzi, 2011;Synnefa, Saliari, & Santamouris, 2012;Zinzi, Carnielo, & Agnoli, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it is important to emphasise that the performance of the roof surface also depends on the thermal emissivity that drives the radiative exchanges of the roof with the sky and the surrounding objects. Several studies were carried out during the past years and showed the potentialities and limits of the technology by means of numerical analyses (Akbari, Bretz, Kurn, & Hartford, 1997;Christen & Vogt, 2004;Suehrcke, Peterson, & Selby, 2008;Synnefa, Santamouris, & Akbari, 2007;Zinzi, 2010) and monitoring in real buildings (Bozonnet, Doya, & Allard, 2011;Carnielo, Fanchiotti, & Zinzi, 2011;Kolokotroni, Gowreesunker, & Giridharan, 2011;Kolokotsa, Diakaki, Papantoniou, & Vlissidis, 2011;Paolini et al, 2013;Parker et al, 1998;Romeo & Zinzi, 2011;Synnefa, Saliari, & Santamouris, 2012;Zinzi, Carnielo, & Agnoli, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Further findings showed that not only could the shades of the paint color affect the reflection of the sunlight, when phase change materials were added to the paints under constant temperature conditions, they could also change the state of matter and provide latent heat to achieve thermal insulation [14]. Some researchers studied the paints with reflection and heat insulation by applying them to a wide variety of buildings and roads [15][16][17][18]. There were also studies on the use of white cement paint, high-gloss reflective gray or white paints, and environmental afforestation on the building rooftops, all aimed to accelerate the light-reflecting of the sunlight.…”
Section: Introductionmentioning
confidence: 99%